PENERAPAN PENDEKATAN JOYFULL LEARNING UNTUK MENINGKATKAN KETERAMPILAN GERAK DASAR LOKOMOR KELAS II PADA MATA PELAJARAN PJOK MIN 2 KOTA PALANGKA RAYA - Kevin Ramadhani Pratama; Rahmad; Sondra Swestyani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Observations on PJOK learning conducted by researchers on class II A MIN 2 Palangka Raya students showed that learning tended to be boring and only centered on the teacher. This condition caused a lack of knowledge and skills of students, especially in locomotor movement material so that special attention was needed in the learning process. This study used a classroom action research (CAR) approach to determine whether student learning outcomes in locomotor movement material could be improved through the application of games and learning media. The study involved 36 class II A MIN 2 Palangka Raya students (19 boys and 17 girls). In cycle 1, the results in aspect 1 showed that students successfully obtained 68% success, aspect 2 had 68%, and aspect 3 had 68% success. This shows a lack of students in applying locomotor movement skills in cycle 1, while in cycle 2 had very satisfactory results with a score of 100% in aspect 1, aspect 2 had 100% completion, and aspect 3 had 100% completion.